THE TEACHER’S STRATEGIES IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Kurniawan, M. Willi; Norawati, Rosinta; Hidayati, Hidayati (Universitas Jambi, 2025)
This study aims to investigate teacher's strategies for teaching English vocabulary to young learners at SDIT As-Syifa Al Inayah 6 Kota Jambi. This study used a qualitative method. This study used three data collection techniques: observation, interviews, and documents. The data was provided by an English teacher who teaches lower-grade students. The data revealed that the teacher used several strategies in teaching vocabulary, separated into two stages. For presenting new words teacher used few strategies such as using picture, using videos and translation. And for the practicing new words teacher used task-based method, games, learners’ active involvement, singing a song, vocabulary notes, and group activity. The strategy that is mostly used in teaching vocabulary is the games, while the strategy that is rarely used is the using videos. this study found factor that influenced teacher when choosing strategies for teaching vocabulary for young learners. The factors that influenced teacher are duration of time, students’ abilities, behavioural control of students, and focus of the activity.